Natural Kaolin: Sustainable Technology for the Instantaneous and Energy‐Neutral Recycling of Anthropogenic Mercury Emissions. Issue 1 (3rd December 2019) - Ganguly, Mainak; Tao, Yuanyuan; Lee, Bryan; Ariya, Parisa A.
Abstract: Kaolin, a natural and inexpensive clay mineral, is ubiquitous in soil, dirt, and airborne particles. Amongst four commonly available clay minerals, kaolin, as a result of its layered structure, is the most efficient natural gaseous Hg adsorbent to date (Langmuir maximum adsorption capacity Q m =574.08 μg g −1 and Freundlich Q m =756.49 μg g −1 ). The Hg uptake proceeds by homogeneous monolayer and heterogeneous processes. Hg physisorption on kaolin occurs in the dark, yet the adsorption rate is enhanced upon irradiation. The effects of several metal complexes, salts, halides and solvents on the Hg uptake were examined. The addition of CuCl2 particles leads to a significant enhancement of the Hg uptake capacity (>30 times) within second timescales and without irradiation. The physisorption with kaolin is switched to chemisorption upon the addition of CuCl2 to kaolin. This process is entirely reversible upon the addition of Zn/Sn granules at room temperature without any added energy. However, the investment of a small amount of renewable energy can speed up the process. This technology demonstrates the facile and efficient capture and recycling of elemental Hg 0 from air. A wide range of metal particles and diverse physicochemical processes, which include the microphysics of nucleation, are herein examined to explore the potential reaction mechanism by using a suite of complementary analytical techniques. These new mechanistic insights open a new era of energy‐neutral environmental remediation based on natural soil/airborne particles. Abstract : Clay, I say ! Kaolin is used for gaseous Hg uptake. Hg physisorption on kaolin occurs in the dark, yet the adsorption rate is enhanced upon irradiation. The effects of several metal complexes, salts, halides, and solvents on Hg uptake are examined. The addition of CuCl2 particles leads to a significant enhancement of the Hg uptake capacity (>30 times) within second timescales and without irradiation.